2018
DOI: 10.1155/2018/3514645
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for the Treatment of Mevalonate Kinase Deficiency

Abstract: Mevalonate kinase deficiency (MKD) is a severe autoinflammatory disease caused by recessive mutations in MVK resulting in reduced function of the enzyme mevalonate kinase, involved in the cholesterol/isoprenoid pathway. MKD presents with periodic episodes of severe systemic inflammation, poor quality of life, and life-threatening sequelae if inadequately treated. We report the case of a 12-year-old girl with MKD and severe autoinflammation that was resistant to IL-1 and TNF-α blockade. In view of this, she com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The effectiveness of etanercept varies among studies, leading to a beneficial response in approximately of 60% of reported patients (14,19). Evidence for the effectiveness of anti-IL-6 therapy in MKD is mainly derived from a few case studies in which tocilizumab, a monoclonal antibody against the IL-6 receptor, resulted in the remission of inflammatory episodes in MKD patients (98)(99)(100)(101). Another study reported four patients, who discontinued tocilizumab treatment because of lack of efficiency (102).…”
Section: Treatment Options For Mkdmentioning
confidence: 99%
“…The effectiveness of etanercept varies among studies, leading to a beneficial response in approximately of 60% of reported patients (14,19). Evidence for the effectiveness of anti-IL-6 therapy in MKD is mainly derived from a few case studies in which tocilizumab, a monoclonal antibody against the IL-6 receptor, resulted in the remission of inflammatory episodes in MKD patients (98)(99)(100)(101). Another study reported four patients, who discontinued tocilizumab treatment because of lack of efficiency (102).…”
Section: Treatment Options For Mkdmentioning
confidence: 99%
“…Literature reviews were performed using "PubMed" and "Web of Science" by searching for the terms "Mevalonate kinase de ciency" and "TNF receptor-associated periodic syndrome" and "tocilizumab". We summarized previously reported cases of tocilizumab treating MKD and TRAPS patients, which showed in Table 2 [15][16][17][18][19][20][21][22] and Table 3 [23][24][25][26]. In previous studies, a total of 11 MKD patients and 4 TRAPS patients were treated with tocilizumab.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tocilizumab has been successfully used in three patients with TRAPS (129)(130)(131) and in seven HIDS/MKD cases (132)(133)(134)(135)(136) in whom anti-TNF and/or anti-IL-1 agents had previously failed. Negative results have been reported in two CAPS (CINCA/NOMID) patients treated with tocilizumab (119,137).…”
Section: Other Autoinflammatory Diseasesmentioning
confidence: 99%